Exponential type convexity and some related inequalities - Mahir Kadakal; İmdat İşcan (Journal of Inequalities and Applications, 2020)
Abstract In this manuscript, we give and study the concept of exponential type convex functions and some of their algebraic properties. We prove two Hermite–Hadamard (H-H) type integral inequalities for the newly introduced class of functions. We also obtain some refinements of the H-H inequality for functions whose first derivative in absolute value at certain power is exponential type convex.